Anti-inflammatory, antimicrobial and antioxidant properties of margaritaria nobilis, stylochiton lancifolius, drypetes principum, crescentia cujete and albizia glaberrima - Jato, Jonathan (2016)
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Philosophy.